Association between erectile dysfunction, cardiovascular risk factors, and coronary artery disease: Role of exercise stress testing and International Index of Erectile Function (IIEF-5) questionnaire. (June 2022) - Ahmed Memon, Shakeel; Adil, Muhammad; Raja Khan, Fahad; Ullah, Safi; Rehmat, Samra; Zad Gul, Nooh
Abstract: Background: The exercise stress test (EST) is a non-invasive investigation to diagnose coronary artery disease. This research aimed to determine the relationship between erectile dysfunction (ED), cardiovascular risk factors, and coronary artery disease (CAD) in men referred for EST. Methods: A prospective cohort study enrolling 303 patients from August 2020 through September 2021. All patients filled out the international Index of Erectile Function (IIEF-5) questionnaire. . They underwent an exercise stress test (EST). A two-tailed independent sample t -test, chi-square tests, and binary logistic regression were used for statistical analysis. Results: EST was positive in 110 (36.3%) patients, negative in 154 (50.8%), and inconclusive in 39 (12.8%) patients. ED was present in 225 (74.3%) patients and absent in 78 (25.8%) patients. 278 (91.7%) had one or more cardiovascular risk factors. This study reported a significant relationship between diabetes mellitus (DM), hypertension (HTN), and the results of EST and ED. Compared to patients without ED, patients with ED had a positive EST result. Definite CAD was diagnosed in 21% of patients with ED compared to 1.3% in patients without ED. For a one-unit increase in age, the odds of ED increased by about 5%. Similarly, a negative EST is compared to a positive EST. Negative EST reduced the likelihood of ED by 82%. Conclusions: This research found a statistically significant connection between CAD, certain cardiovascular risk factors, and ED using the EST and IIEF-5 questionnaires. This research is significant because it may alter the way cardiovascular risk stratification is done.